Sequências didáticas e canteiros de ervas aromáticas : estratégias para aprendizagem significativa de conteúdos botânicos no ensino médio - Prado, Edman Weverton do (2018)
The lack of practical activities and attractive didactic material represents an obstacle to the teaching-learning process, generating students' lack of interest. In this sense we highlight as an option the Active Methods of Teaching through teaching learning sequence developed in alternative environments. One of these environments can be the garden, because it allows the integration between students and the visualization of concepts and processes presented in the classroom, becoming an outdoor laboratory. We start from the idea that the vegetable garden has the potential as a living laboratory, where practical activities can be carried out connected to the daily life of the students. In addition, this environment enables the development of concepts related to Environmental Education and enhancement of Ethno-cognitions. Our objective was to present, test and evaluate a didactic sequence for the study of the Plant Kingdom. We use a qualitative approach, through Research-Action and we opted for a mixed data collection, following a built-in methodological design. The first part of the research investigated learning demands with science and biology teachers and from there we built an educational product. The second part consisted of the application of the didactic material produced, with a 3rd grade high school class as a focus group. The results of the first part point to a lack of knowledge of alternative teaching methods and to students 'lack of interest as the main obstacle to the teaching-learning process, reinforcing the need to produce more attractive materials and connected to students' daily lives. In the second part, we could see that the use of the proposed didactic material made the class more dynamic and interesting, the students' attitudes and reports were positive regarding the new methods presented.